The industrially important genus Kaempferia: An ethnopharmacological review - Singh, Arpit; Singh, Nitesh; Singh, Sanchita; Srivastava, Ravi Prakash; Singh, Lav; Verma, Praveen C.; Devkota, Hari P.; Rahman, Laiq ur; Kumar Rajak, Bikash; Singh, Amrita; Saxena, Gauri (Frontiers in Pharmacology, 2023)
Kaempferia, a member of the family Zingiberaceae, is widely distributed with many of its species being found in Asia. These plants have important ethnobotanical significance as many species are used in Ayurvedic and other traditional medicine preparations. This genus has received a lot of scholarly attention recently as a result of its numerous health advantages it possesses. In this review, we have compiled the scientific information regarding the relevance, distribution, industrial applications, phytochemistry, ethnopharmacology, and tissue culture of medicinal plants of Kaempferia genus along with cultivation and conservation initiatives. The current review provides a richer and deeper understanding of Kaempferia, which can be applied in areas like phyto-pharmacology, molecular research, conservation biology and industrial biology.